Replicability and scalability of mini-grid solution to rural electrification programs in sub-Saharan Africa. (June 2017) - Azimoh, Chukwuma Leonard; Klintenberg, Patrik; Mbohwa, Charles; Wallin, Fredrik
Abstract: The assessment of off-grid electrification programs in developing countries largely based on mini-grid and solar home system (SHS) has shown that they are faced with low development imparts and sustainability challenges, which has resulted in failure of many projects. This study provides solutions on how to surmount these challenges, leaning on the experience of a hybrid solar-diesel mini-grid at Tsumkwe village in Namibia. It provides analyses of a case study based on empirical evidence from field studies, interviews of representatives of households, public institutions and energy providers. In addition, it investigates the technical challenges and economic impacts of the electrification program. HOMER™ and MATLAB™ models were used in the analysis and investigations. The findings show that despite the challenges, the system has been sustained because it keyed into an existing structure with growth potentials. The progressive tariff system adopted by the government helped to cushion costs and allow low income households in the energy matrix. Adoption of strict maintenance measures, and implementation of energy efficiency measures prior to the commissioning of the program, resulted in the reduction of costs. The success elements identified in this study could be extrapolated in other sub-Saharan African countries if the challenges are properly addressed. Highlights: Field based assessment of an off-grid solar-diesel mini-grid system. Essential elements for the sustainability of off-grid rural electrification. Energy efficient measures contributes to successful rural electrification programs. Progressive tariff system encourages low income users to be in the energy matrix. Prepaid metering provided best option for revenue collection in rural electrification programs.